Penguatan Kemampuan Wacana Kritis Siswa Ponpes Al-Falah dalam Menghadapi Informasi di Era Post-Truth - Argariawan Tamsil; Nuramila Nuramila; Ayu Hidayanti Ali (Jurnal Pengabdian Masyarakat, 2026)
Language is never a neutral medium; it is always intertwined with power relations, ideology, and social practice. In today’s digital society, this dynamic has grown more complex with the rise of the post-truth era, where objective facts are frequently overshadowed by emotional narratives, virality, and the pursuit of online attention. This community service program sought to enhance students’ Critical Discourse Analysis (CDA) skills in navigating the intense flow of digital information, particularly at Pondok Pesantren Al-Falah Gorontalo. The initiative adopted a reflective and educative approach that positioned students as active participants in examining, interpreting, and evaluating various forms of discourse. Activities included conceptual presentations, interactive discussions, and the analysis of real digital content such as sensational headlines, viral posts, and decontextualized images. Through these methods, students were encouraged to recognize that information is never neutral and always reflects certain interests and perspectives. The findings showed that participants became more aware of shifting discourse power relations in the digital age, moving from traditional vertical authority structures to more horizontal interactions among users. They began to see CDA not merely as theoretical knowledge, but as a practical framework for understanding everyday digital realities. Strengthening CDA skills fostered critical reflection, increased vigilance toward misinformation, and heightened ethical awareness as both consumers and producers of online content. Ultimately, integrating CDA into educational settings, especially Islamic boarding schools, serves as a strategic effort to cultivate responsible, critical individuals capable of understanding and responding thoughtfully to discursive practices in digital spaces.